Nominal versus real wage rigidities: A Bayesian approach - Pau Rabanal; Juan F. Rubio-Ramírez (Federal Reserve Bank of Atlanta, 2001)
This paper explores the capability of a dynamic stochastic general equilibrium model with staggered price setting and real wage rigidities to fit the data with reasonable average durations of price and wage contracts. The authors implement a Bayesian approach for parameter estimation and for model comparison with other models that only incorporate nominal rigidities. Their main results can be summarized as follows: First, the authors find that, on average, prices are fixed for three quarters, nominal wages are fixed for five quarters, and half of the wage setters follow a real wage indexing rule of thumb. Second, when the authors remove real wage rigidities and reestimate the model, the parameter on price duration increases. Hence, the lack of endogenous persistence due to real wage rigidities is substituted by a high degree of price stickiness. Third, the authors find little evidence of backward-looking behavior in price inflation. Finally, using the marginal likelihood as a comparison criterion, their model performs best.
Keywords: 330; Wages; Econometric models